Analisis Kesalahan Kata dalam Teks Berita Kompas.Com Edisi Februari 2025 - Dama, Ratna Gole; Kami, Kanisius; Gena, Engel Bertha Helena (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to find and describe the errors of words contained in Kompas.Com news text. The type of research used in this study is a type of descriptive research. The data in this study are quotes that contain word errors. The source of data in this study is the text of the news in the February 2025 edition of Kompas.Com. The data collection technique in this study is to read news texts and record word errors. The data analysis technique in this study is to identify the data found, group the data according to the type of word error and make improvements to each data that contains word errors. Based on the results of a study whose discussion of word errors in news texts Kompas.Com, researchers found 29 data. Of the 29 data, it was found that there were 10 errors and 19 errors, which can be detailed as follows: a) Errors: errors in the use of non-standard words as many as 10 data, in the form of: 1) detergent, 2) sandpaper, 3) sharia, 4) omnivore, 5) jars, 6) claiming, 7) ramadan, 8) wantin, 9) boarding house, and 10) laziness. b) Mistake: word writing errors of 15 data (loss of phonemes as many as 5 data, in the form of: 1) Beral, 2) inferred, 3) deajat, 4) follow-up, and 5) offer. The addition of phonemes as many as 5 data, in the form of: 1) Dilimbau, 2) meznjadi, 3) bank, 4) distributors, and 5) terlkihat. Phoneme changes as many as 5 data, in the form of: 1) Fatigue, 2) thanksgiving, 3) being stuck, 4) meha, and 5) nerapa), and incorrect use of words as many as 4 data, in the form of: 1) di, 2) to, 3) send, and 4) Saturday.